Weather, food and predation shape the timing of Marsh Tit breeding in primaeval conditions: a long-term study - Wesołowski, Tomasz (Journal of ornithology, 2023)
Marsh Tits Poecile palustris were studied in primaeval fragments of Białowieża National Park (Poland) between 1997 and 2020 to investigate how variation in spring weather, predation, and the timing of tree bud burst and emergence and development of folivorous caterpillars impacts reproductive performance. Marsh Tits commenced egg laying earlier in warmer springs, but had only limited capacity to adjust their breeding behaviour in response to varying conditions in the nestling period. Despite folivorous caterpillars constituting an important food source for nestlings, Marsh Tits reproduced successfully even in years of very low caterpillar abundance, provided the weather remained good and predator pressure was low. Caterpillar abundance became important only in colder springs, when signs of undernourishment (higher brood reduction rates, delayed fledging) were observed. Malnourished young also appeared more exposed to predation as an indirect effect of food availability and weather contributing to nesting success. Despite predation, Marsh Tits experienced median annual nest losses of only 27.5%. Egg laying commenced and breeding finished ahead of most other local bird species, probably due to intraspecific competition to produce young before other birds in the population. Such timing seemingly created a safety window, when predators were likely not yet searching for nests, resulting in nest losses before hatching of usually below 10%. Across the 24 years of this study, Marsh Tits were exposed to a wide range of conditions that themselves did not show a temporal trend. As such, the observed variation is probably representative of forests not subject to climate warming.